Operative Time, Length of Stay, Short-Term Readmission, and Complications after Hinged Primary Total Knee Arthroplasty: A Propensity Score Matched Analysis - Sodhi, Nipun; Patel, Yatindra H.; George, Jaiben; Sultan, Assem A.; Anis, Hiba K.; Newman, Jared M.; Kryzak, Thomas J.; Khlopas, Anton; Moskal, Joseph T.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Despite the wide utilization of total knee arthroplasty (TKA), it can be technically challenging to perform in patients who have concomitant bone loss, ligamentous laxity, or high-grade deformity, whether in a revision situation or due to a primary pathology. Therefore, hinged knee prostheses have been developed to provide more stable fixation in these situations. The purpose of this study was to compare the short-term peri- and postoperative outcomes of patients undergoing primary TKA with and without hinged prosthesis. Specifically, we compared (1) mean operative times, (2) lengths of stay (LOS), (3) 30-day readmissions, and (4) complications. The American College of Surgeons National Surgical Quality Improvement Program database was queried to identify hinged TKAs and 99 procedures were included. They were matched in a 1:3 ratio to primary TKAs without a hinged prosthesis using propensity score matching. Operative time, LOS, discharge disposition, 30-day readmissions, and complications were compared. Adjusted odds ratios (OR) were also calculated. The operative time was significantly higher in hinged cohort compared with the nonhinged cohort (mean difference [MD] = 22 minutes; range, 10–34 minutes, p < 0.001). There were no significant differences between hinged and nonhinged TKAs with respect to LOS (MD= 0.61 days, range, –0.07–1.30 days, p = 0.080), discharge disposition (OR = 1.09, 95% confidence interval [CI], 0.66–1.84), readmissions (OR = 2.67, 95% CI, 0.84–8.24), and any complications (OR = 1.13, 95% CI, 0.55–2.19). Not surprisingly, primary TKAs with hinged prostheses had increased operative times, but had similar LOS, discharge dispositions, and 30-day rates of readmission and complications when compared with TKAs without a hinged prosthesis. One potential contributing factor to the increased operating time is that patients who receive a hinged implant tend to present with more severe deformities. It is reassuring to know that early outcomes were similar between both cohorts (although we await longer follow-up studies), and that hinged implants can be considered in these difficult to treat patients.
Keywords: hinged; total knee arthroplasty; outcomes; length of stay; readmissions